Implementasi LDA pada fitur HOG untuk Klasifikasi ASL Menggunakan K-NN - Muhammad Ezar Al Rivan; Hafiz Irsyad; Kevin Kevin; Arta Tri Narta (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
Sign Language is alternative way to communication using sign. One of sign language is American Sign Language (ASL). Image from Dataset processed using feature extraction HOG then reduce using Linear Discriminant Analysis (LDA). The reduced feature used to K-Nearest Neighbor classification. There are 3 distance used consist of euclidean, manhattan and chebyshev. The best accuracy obtain from manhattan distance using k=3 with 72,42% precision.